Generation of Useful Hydrocarbons and Hydrogen during Photocatalytic Decomposition of Acetic Acid on CuO/Rutile Photocatalysts. (21st May 2009) - Mozia, Sylwia
Abstract : The presented studies have focused on a photocatalytic generation of useful hydrocarbons, mainly methane and ethane, from acetic acid under N 2 atmosphere. CuO-loaded rutile, as well as unmodified rutile and anatase-phase TiO 2 photocatalysts were applied in the experiments. The efficiency of the catalysts towards methane generation changed in the following order: Cu-TiO 2 (10% Cu) > crude TiO 2 ≈ Cu-TiO 2 (20% Cu) > Cu-TiO 2 (5% Cu) > rutile. The amount of CH 4 produced in the presence of the catalyst containing 10 wt% of Cu was higher for ca. 33% than in case of pure rutile. The concentration of ethane was 14–16 times lower than the amount of methane, regardless of the catalyst used. Low concentrations of hydrogen were also detected in the gaseous mixtures. After 5 hours of the process conducted with the catalyst containing 5–20 wt% of Cu the concentration of hydrogen amounted to 0.06–0.14 vol.%, respectively.